Pengaplikasian Literasi Wirausaha Digital Yang Mendorong Tumbuhnya Motivasi Pengembangan Usaha Santanamekar Kabupaten Tasikmalaya - Adi Prehanto; Btari Mariska Purwaamijaya; Oding Herdiana; Muhammad Dzikri Ar Ridlo; Adam Hermawan; Alifia Fatimatun Nazya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The industrial revolution 4.0 has brought many developments, the era of automation has been implemented in several sectors to make activities more effective and artificial intelligence is the driving force in this era, which promises many conveniences in various fields. Based on the results of research entitled